A common monitoring framework for ending preventable maternal mortality, 2015–2030: phase I of a multi-step process. Issue 1 (December 2016) - Moran, Allisyn; Jolivet, R.; Chou, Doris; Dalglish, Sarah; Hill, Kathleen; Ramsey, Kate; Rawlins, Barbara; Say, Lale
Abstract Background While global maternal mortality declined 44 % between 1990 and 2015, the majority of countries fell short of attaining Millennium Development Goal targets. The Sustainable Development Goals (SDGs), adopted in late 2015, include a target to reduce national maternal mortality ratios (MMR) to achieve a global average of 70 per 100, 000 live births by 2030. A comprehensive paper outliningStrategies toward Ending Preventable Maternal Mortality (EPMM) was launched in February 2015 to support achievement of the SDG global targets. To date, there has not been consensus on a set of core metrics to track progress toward the overall global maternal mortality target, which has made it difficult to systematically monitor maternal health status and programs over time. Findings The World Health Organization (WHO), Maternal Health Taskforce (MHTF), and the US Agency for International Development (USAID) along with its flagship Maternal and Child Survival Program (MCSP), facilitated a consultative process to seek consensus on maternal health indicators for global monitoring and reporting by all countries. Consensus was reached on 12 indicators and four priority areas for further indicator development and testing. These indicators are being harmonized with the Every Newborn Action Plan core metrics for a joint global maternal newborn monitoring framework. Next steps include a similar process to agree upon indicators to monitor social, political and economic determinants of maternal health and survival highlighted in the EPMM strategies. Conclusion This process provides a foundation for the maternal health community to work collaboratively to track progress on core global indicators. It is important that actors continue to work together through transparent and participatory processes to track progress to end preventable maternal mortality and achieve the SDG maternal mortality targets.